Recent Patents on EDM of Nonconductive Materials - Xie, Baocheng; Wang, Yi (Recent Patents on Mechanical Engineering, 2021)
Background: The non-conductive materials are widely applied in electronics, optics, instrumentation, aerospace, national defense and civil industry because of their strong wear resistance, high hardness and good insulation performance. However, it is difficult for traditional machine methods to process the non-conductive materials. Electrical Discharge Machining (EDM), as a nontraditional advanced processing technology, is an alternative method for machining the non-conductive materials. Therefore, the development trend of EDM of non-conductive materials has been paid more and more attention. Objective: To meet the growing processing requirement of processing efficiency and processing quality of EDM of non-conductive materials, the processing devices and processing methods of EDM of nonconductive materials, such as high-voltage spark machining, auxiliary electrode spark machining and electrolysis spark discharge machining are being improved continuously. Methods: This paper retraces various current representative patents relative to high-voltage spark machining, auxiliary electrode spark machining and electrolysis spark discharge machining of nonconductive materials. Results: Through investigating a large number of patents on EDM of non-conductive materials, the main current existing problems, such as low processing efficiency and poor processing quality, are summarized and analyzed. Moreover, the development tendency of EDM of non-conductive materials in the future is also discussed. Conclusion: The optimization of processing devices and processing methods of EDM of nonconductive materials are conducive to improve processing efficiency and processing quality. More correlative patents will be invented in the future.
Keywords: processing efficiency